PENGARUH PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG DAN MODAL KERJA TERHADAP PROFITABILITAS PADA PT. KESUMA MAKMUR KONSTRUKSINDO PERIODE 2014 - 2018 - BAHRUM NAZ SITEPU (JURNAL ILMIAH KOHESI, 2021)
The goal of the company is to increase the company value one of the way is to increase the quality of profit. Inventory,receivable, and working capital are the part of current assets which continuously experiencing rotation. Receivable andinventory have an important role for the company through the management of inventory receivable effectively and efficientlyso that the capital needed smaller and can found high levels of profitability. The purpose of this study is to test and analyzethe effect of inventory turnover, receivable turnover and working capital on profitability at PT. Kesuma MakmurKonstruksindo. The subject of this research is customer of PT. Kesuma Makmur Konstruksindo which is located at JalanLetda Sujono No. 120, Medan. The sample in this research is 5 years financial report of PT. Kesuma Makmur Konstruksindoby using sampling saturated data obtained as much as 60 data. The results showed that inventory turnover, receivableturnover and working capital effect on profitability at PT. Kesuma Makmur Konstruksindo. From the results of coefficient ofdetermination test shows that 27 % profitability which can be explained by the variation of two independent variables usedare inventory turnover, receivable turnover and working capital while the remaining 73 % is explained by other variables thatare not used in this study eg Debt to equity ratio and operational costs.